2001
DOI: 10.1001/archneur.58.6.874
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity, Hippocampal Place Cells, and Cognitive Maps

Abstract: Memory of even the briefest event can last a lifetime. Thus, learning and memory require neuronal mechanisms that allow rapid, yet persistent, changes to brain circuits. Hippocampal neuropsychology, synaptic and cellular electrophysiology, pharmacology, and molecular genetics converge and begin to reveal these mechanisms. Lesions of the hippocampus profoundly impair memory for recent events in humans and rodents. Circuits within the hippocampus are remarkably plastic, and this plasticity is mediated in part th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
73
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 25 publications
3
73
0
1
Order By: Relevance
“…Activation of NMDA receptors increase in‰ux of extracellular calcium in the neuronal cells, thereby increasing free intracellular calcium, which binds to calmodulin and subsequently stimulates relevant gene expression that eventually leads to enhancement of short term and long term memory. [48][49][50] Therefore, it may be possible that the observed ameliorative eĆ ect of statins on Alprazolam induced amnesia may be mediated through enhanced brain level of NO and through activation of NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NMDA receptors increase in‰ux of extracellular calcium in the neuronal cells, thereby increasing free intracellular calcium, which binds to calmodulin and subsequently stimulates relevant gene expression that eventually leads to enhancement of short term and long term memory. [48][49][50] Therefore, it may be possible that the observed ameliorative eĆ ect of statins on Alprazolam induced amnesia may be mediated through enhanced brain level of NO and through activation of NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that these manifestations of aging occur sequentially suggests a model of hippocampal aging that can be related to neurobiological changes in hippocampal circuitry during aging. Rigidity, delayed control by external cues, and multi-stability When moved from a familiar environment to a novel one, hippocampal neurons of young rats rapidly develop spatial representations that are unrelated to those of the familiar environment, and these representations are strongly under the control of salient visual landmarks (Wilson and McNaughton, 1993;Shapiro, 2001). Previous experiments have demonstrated that hippocampal cells of aged rats abnormally maintain existing spatial representations over multiple experiences despite alterations in environment or task demands sufficient to induce new representations in young rats during the first experience (Tanila et al, 1997b;Oler and Markus, 2000;Wilson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampus is a major anatomical substrate of memory (Eichenbaum, 2004;Shapiro, 2001), and its structural and functional abnormalities predict Alzheimer's disease (AD) (Glodzik-Sobanska et al, 2005;Mosconi, 2005). As hippocampal cornu ammonis sector1 is highly sensitive to both AD pathology and ischemia (Zarow et al, 2005), the presence of vascular risk can strongly compound on AD-related damage.…”
Section: Introductionmentioning
confidence: 99%